An Overview of Methods to Characterize Skin Type: Focus on Visual Rating Scales and Self-Report Instruments - Rita Oliveira; Joana Ferreira; Luís Filipe Azevedo; Isabel F. Almeida (Cosmetics, 2023)
Skin type classification is important because it provides guidance for professionals and consumers to recommend and select the most appropriate cosmetic products and skin care protocols and it is also important in clinical research. Several methods have been proposed for classifying skin typologies such as non-invasive bioengineering tools (examples: Corneometer® and Sebumeter®), visual and tactile methods (subjective methods that evaluate skin appearance, texture, temperature, and abnormalities), artificial intelligence-based tools and instruments (examples: visual rating scales, and self-report instruments). Examples of known visual rating scales used to classify skin aging are the Griffiths Photonumeric Scale, the Glogau Scale, and the SCINEXA Scale. The Fitzpatrick Skin Phototype Classification and the Baumann Skin Type System are some of the self-report instruments used for skin type classification. Despite the diversity of methods to classify skin type and degree of skin aging, data on instruments are scarce and not adequately compiled. Validation in larger samples and with individuals of different ethnicities and geographic locations is needed to promote a more universal use. Visual rating scales and instruments are interesting tools that allow the skin to be promptly and efficiently examined, without using costly or complex equipment, and are very useful in a clinical or self-assessment context.